Social policy or crowding-out? Tenant protection in comparative long-run perspective - Konstantin A. Kholodilin; Sebastian Kohl; Yulia Prozorova; Julien Licheron (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
In the shadow of homeownership and public housing, social policy through the regulation of private rental markets is a neglected and underestimated field of social policy. This paper, therefore, presents unique new data on the development of private tenancy legislation through the binary coding of rent control, the protection of tenants from eviction, and rental housing rationing laws across more than 25 countries and 100 years. This long-run perspective reveals the dynamic effects of rent control on the rise of homeownership as the dominant tenure during the 20th century. We find that both rent regulation and rationing legislation effectively increased homeownership, but only up to a certain threshold. We suggest that the short-term lure of an inexpensive social policy for tenants has led to the long-term marginalization of rental markets in many countries.
Keywords: C23; O18; R38; 330; homeownership; rent control; tenure security; housing rationing; dynamic panel data model